Knowledge And Attitudes Of Prospective Brides Before And After Counseling On Preconceptive Nutrition - Febthia Rika Ramadhaniah (Jurnal Kebidanan Sorong, 2022)
Severe maternal nutrition before pregnancy can lead to Intrauterine Growth Restriction (IUGR), Neural Tube Defects (NTDs) and increasing the risk of illness and death. In West Kalimantan the number of pregnant women at risk of KEK reached 29.7%. In 2015, cases of IUGR in Pontianak reached 414 people from 12,047 inhabitants. Behavior of preconception women to prepare their pregnancy may reduce the risk of pregnancy. Knowledge and attitude can increase that behavior. One of the efforts to increase knowledge and attitude is through counseling. Objective: to determine the comparison of knowledge and attitude before and after health education about preconception nutrition for preconception women. Method: quasi experiment by pre and post test design without control. The subjects are 40 preconception women by using consecutive sampling technique. The research instrument used questionnaire. Results: univariate analysis showed knowledge of preconception women before health education was 55% enough and after health education became 100% knowledgeable. The attitude of the women before health education was 42.5% negative and after health education became 67.5% positive. Bivariate analysis was using wilcoxon, obtained p <0,05. Conclusion: there are the comparison of knowledge and attitude before and after health education about preconception nutrition for preconception women